Application based of Tourist Attraction Selection with Fuzzy Tahani - Sari Rochman, Eka Mala; Pratama, Ifan; -, Husni; Rachmad, Aeri (Jurnal Pekommas, 2020)
Madura is one of the islands located in the Province of East Java, Indonesia, which has a lot of tourism potency but there has been no system to accommodate this. As a result, the tourists have difficulty of getting the official information about tourism objectives within Madura. Therefore, in this study was conducted with the aim of creating a decision support system for tourism object selection in Madura so that the prospective tourists find it easier to choose tourism attractions that that suits their desires. In connection with these objectives, this study applies the Fuzzy Tahani logic method as the decision support model. It is used because its main equipment is a functional hierarchy that its main input is predetermined criteria.  The results of this study are expected to facilitate prospective tourists in making decisions in choosing attractions in Madura. By using the visitor criterias, the distance from the city center, and the reviews of the tourists on the attractions, the decision support system is able to provide recommendations for tourist attractions to be selected. The result of the functionality test showed determined that the system can 100% run.